Participative Leadership: A Literature Review and Prospects for Future Research - Wang, Qiang; Hou, Hong; Li, Zhibin (Frontiers in Psychology, 2022)
Changes in the external market environment put forward objective requirements for the formulation of organizational strategic plans, making it difficult for the organization’s leaders to make the right and effective decisions quickly on their own. As a result, participative leadership, which encourages and supports employees to participate in the decision-making process of organizations, has received increasing attention from both theoretical and practical circles. We searched the literature related to participative leadership in databases such as Web of Science, EBSCO, ProQuest, and China National Knowledge Infrastructure (CNKI). Based on this, we clarify the concept of participative leadership, propose a definition of participative leadership, summarize measurement scales for this type of leadership, and compare participative leadership with other leadership styles (empowering leadership and directive leadership). We also present a research framework for participative leadership that demonstrates its antecedents; the mechanisms for its development based on social exchange theory, conservation of resources theory, social cognitive theory; social information processing theory, and implicit leadership theory; and outcomes. Finally, we identify five potential research areas: Connotation, antecedents, outcomes, mediator and moderators, and Chinese localization research on participative leadership.